If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -6(3y + -11) = 0 Reorder the terms: 6y + -6(-11 + 3y) = 0 6y + (-11 * -6 + 3y * -6) = 0 6y + (66 + -18y) = 0 Reorder the terms: 66 + 6y + -18y = 0 Combine like terms: 6y + -18y = -12y 66 + -12y = 0 Solving 66 + -12y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-66' to each side of the equation. 66 + -66 + -12y = 0 + -66 Combine like terms: 66 + -66 = 0 0 + -12y = 0 + -66 -12y = 0 + -66 Combine like terms: 0 + -66 = -66 -12y = -66 Divide each side by '-12'. y = 5.5 Simplifying y = 5.5
| 2v+7v=-9 | | 13x-7=3(4x+5)-8 | | x-21/2 | | -11+51=-5(x+2) | | m+8+6=22 | | x=-3y-8y+3x-9 | | 2x+2=35+5x | | y-3y-10=0 | | 4a+3+2a=15 | | 5(d-5)+12= | | -13=2m+1 | | 7-2x-5-10x=5 | | p=2(d+w) | | -3(n+7)= | | 2x^2-5x+6=1 | | -69-4z=3+5x | | f^5-20/4+12+2^3 | | 5=5x-2 | | x-0.15+10.00=180 | | 1/5(x+4)=-5 | | 12x+3+45=180 | | -12=3+x | | 6(r-5)= | | 2/3n+2=16 | | 1/2(x+1)=16 | | 4x-5=1+6x | | 3z+31=-2z+16 | | -5(n-1)=60 | | 5(3x+1)=2x-7 | | b(b-3)=b+12 | | -2x+6y=20 | | 3xy-2x=y |